Influence of the Prosumer Allocation and Heat Production on a District Heating Network - Ancona, Maria Alessandra; Bianchi, Michele; Branchini, Lisa; De Pascale, Andrea; Melino, Francesco; Peretto, Antonio; Rosati, Jessica (Frontiers in Mechanical Engineering, 2021)
To face the climate change and global warming issues, European countries have set new targets in order to reduce the CO2 emissions by 40 % to 2030 and by 80 % to 2050. The District Heating Networks, and in particular low temperature networks, due to their efficient heat supply and distribution represent a key point for meeting these goals, as well as the renewable sources integration. Nowadays, in fact, about 40 % of the energy consumed in Europe is for heating, most of which is provided by fossil fuels employment. This paper concerns the Smart District Heating, namely the possibility of a bidirectional energy exchange between the district heating network and the connected users. The main purpose of this study is to evaluate the possibility of including a prosumer – i.e. a customer who can both consume and produce heat – in an existing small/medium district heating network. To this purpose, an in-house developed software has been applied to analyze whether and which user of the district heating network is more suitable to be set as prosumer and the effect of the installed distributed generation system on the network. The results show how the choice of a prosumer over another and how the amount of exchanged thermal power affect the performance of the network, with a consequent need of a modification in its operation and management.